ASPEK HUKUM PRUDENTIAL PRINCIPLE DAN THE FIVE C OF CREDIT ANALYSIS DALAM PEMBERIAN KREDIT TANPA AGUNAN OLEH BANK DAN AKIBAT HUKUMNYA - fanny angelina (Humani (Hukum dan Masyarakat Madani), 2020)
The increasingly consumptive needs of the community have made banks issue a banking product that can make it easier for the community, namely Unsecured Credit (KTA). This study aims to determine the legal consequences of not applying the prudential principle and the five C of credit analysis on the provision of unsecured loans. This study uses a normative juridical research method. The nature of this research is descriptive analytical which describes the legal aspects related to bank credit agreements, especially for unsecured loans. The research data was obtained normatively which was described by describing the data obtained from the literature study. In providing Unsecured Loans, banks must apply the prudential principle (Prudential Principle). The failure to apply this banking principle has risks and legal consequences that are reflected in the existing regulations.